ChemInform Abstract: Synthetically Important Alkali‐Metal Utility Amides: Lithium, Sodium, and Potassium Hexamethyldisilazides, Diisopropylamides, and Tetramethylpiperidides. Issue 8 (25th February 2014) - Mulvey, Robert E.; Robertson, Stuart D.
Abstract Review: 98 refs.